The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1073/pnas.0706914105
|View full text |Cite
|
Sign up to set email alerts
|

Dodecamer rotor ring defines H + /ATP ratio for ATP synthesis of prokaryotic V-ATPase from Thermus thermophilus

Abstract: ATP synthesis by V-ATPase from the thermophilic bacterium Thermus thermophilus driven by the acid-base transition was investigated. The rate of ATP synthesis increased in parallel with the increase in proton motive force (PMF) >110 mV, which is composed of a difference in proton concentration (⌬pH) and the electrical potential differences (⌬⌿) across membranes. The optimum rate of synthesis reached 85 s ؊1 , and the H ؉ /ATP ratio of 4.0 ؎ 0.1 was obtained. ATP was synthesized at a considerable rate solely by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 39 publications
4
72
1
Order By: Relevance
“…Our analysis suggests that variant experimental conditions likely underlie conflicting evidence regarding kinetic equivalence of pmf components Δ pH and Δψ. Some in vitro studies have found that the effect of the two components of pmf are equivalent (39)(40)(41)(42), whereas others have concluded that they are not (43)(44)(45). There is no inherent reason to expect kinetic equivalence (53) because Δ pH and Δψ affect kinetics through different mechanisms: Δ pH through H + concentration, and Δψ most likely through binding affinity dictated by the thermodynamic cycle constraint, as described in SI Appendix.…”
Section: Kinetic Equivalence Of Pmf Components May Depend On Experimementioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis suggests that variant experimental conditions likely underlie conflicting evidence regarding kinetic equivalence of pmf components Δ pH and Δψ. Some in vitro studies have found that the effect of the two components of pmf are equivalent (39)(40)(41)(42), whereas others have concluded that they are not (43)(44)(45). There is no inherent reason to expect kinetic equivalence (53) because Δ pH and Δψ affect kinetics through different mechanisms: Δ pH through H + concentration, and Δψ most likely through binding affinity dictated by the thermodynamic cycle constraint, as described in SI Appendix.…”
Section: Kinetic Equivalence Of Pmf Components May Depend On Experimementioning
confidence: 99%
“…Green arrows represent range of productive operating condition for each of the ATPases shown. Red circles represent examples of reported stoichiometry and physiological conditions (42,48,60,61,(63)(64)(65)(66)(67). The diagonal represents equilibrium behavior where the efficiency, as defined in the text, is maximum but the rate of synthesis or pumping would vanish.…”
Section: Kinetic Equivalence Of Pmf Components May Depend On Experimementioning
confidence: 99%
See 1 more Smart Citation
“…3B) further supports the hypothesis that the map represents an average sampled from images of particles that have been trapped with the rotor in a single position. The L-subunit is known to form a dodecameric ring (14). Automatic docking of a comparative model of the L 12 -ring positioned the ring with the connecting loops of the transmembrane helices of the L-subunits facing towards the V 1 region (Fig.…”
Section: Subunit C Of the Central Stalk And Its Interaction With The mentioning
confidence: 99%
“…Instead of a single peripheral stalk, as found in the F-type ATP synthase (11,12), V-ATPases have more than one peripheral stalk, each consisting of an EG heterodimer in T. thermophilus (13). The c-ring in F O is homologous to the c-ring of eukaryotic V-ATPase and the L 12 -ring of the T. thermophilus enzyme (14), whereas the membrane-bound a-subunit contains an additional N-terminal domain in V-ATPase and is called subunit I in the T. thermophilus enzyme. The C-subunit of T. thermophilus forms a part of the central stalk unique to the V-ATPase family, coupling V 1 to the proteolipid-ring of L-subunits (15).…”
mentioning
confidence: 99%